Therapeutic Effect of Ghrelin in the Course of Ischemia/Reperfusion-Induced Acute Pancreatitis - Bukowczan, J.; Warzecha, Z.; Ceranowicz, P.; Kusnierz-Cabala, B.; Tomaszewska, R.; Dembinski, A. (Current Pharmaceutical Design, 2015)
Background: Protective effect of pretreatment with ghrelin against different forms of acute pancreatitis (AP) has been recently reported. Moreover, the healing properties of this peptide have been proved in AP evoked by cerulein. However, no studies have investigated whether the administration of ghrelin affects the course of ischemia/reperfusion-induced AP. Aim: The aim of this study was to evaluate the impact of ghrelin therapy on the course of necrotizing inflammation of the pancreas and to test its impact on peroxidation of lipids and antioxidant defense system in the acutely inflamed pancreas. Methods: Acute inflammation of the pancreas was triggered by pancreatic ischemia which was then followed by reperfusion of the gland. Ghrelin (8nmol/kg/dose) was administered to intraperitoneally twice daily, 24h after the initiation of AP. The impact of ghrelin on the course of necrotizing pancreatitis was evaluated between 1 and 21 days, and involved histological, functional, and biochemical analyses. Results: Treatment with ghrelin ameliorated morphological signs of pancreatic damage including edema, acinar cells vacuolization, hemorrhages, acinar necrosis, leukocytic infiltration of the gland, and led to its earlier regeneration. These effects were accompanied by an improvement in pancreatic blood flow, enhanced DNA synthesis, reduced serum level of pro- inflammatory interleukin-1β, decreased levels of malondialdehyde and an enhanced superoxide dismutase activity in pancreatic tissue. Conclusions: Ghrelin exerts a pronounced therapeutic effect against ischemia-reperfusion-induced pancreatitis. The mechanisms involved are likely multifactorial and are mediated by its anti-inflammatory, as well as anti-oxidative properties.
Keywords: malondialdehyde